Avaliação dos parâmetros tempo, corrente e pressão na soldagem por resistência elétrica de compósitos PEI/fibras contínuas: Influência na resistência mecânica - Abrahão, Ana Beatriz Ramos Moreira [UNESP]; Reis, Jonas Frank; Brejão, Samia Danuta [UNESP]; Ribeiro, Vinícius Garcia; Costa, Michelle Leali [UNESP]; Botelho, Edson Cocchieri [UNESP] (My University, 2015)
Nowadays, many components applied in the aerospace industry, which had been previously used with thermoset matrix composites, are being replaced by those with thermoplastic matrix, which is mainly due to having better mechanical properties, the possibility of reuse and ease in manufacturing large and complex parts which will be integrated to form the desired component with higher service temperature. However, a major problem concerning the use of polymer composites for structural applications consists in its effective integration of components. Electrical resistance welding has been considered as one of the most promising techniques for bonding thermoplastic composites because it is a quick process with little surface preparation. The main objective of this work is to study the resistance welding parameters for PEI (polyether imide), and carbon and glass (hybrid) fibers laminates for aeronautical applications. The composite specimens were welded and subjected to the lap shear test in order to establish the most suitable variable in this process. It was used a full factorial design that allowed, with fewer experiments, exploring the whole experimental area of interest, establishing values of electric current, pressure and time for the studied welding process.
Evaluation of current, pressure and time parameters in electrical resistance welding of PEI/continuous fibers composites: Influence on mechanical resistance